2018
DOI: 10.3390/genes9080415
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Candidate Markers of Type 2 Diabetes and Obesity in Russia by Exome Sequencing with a Limited Sample Size

Abstract: Type 2 diabetes (T2D) and obesity are common chronic disorders with multifactorial etiology. In our study, we performed an exome sequencing analysis of 110 patients of Russian ethnicity together with a multi-perspective approach based on biologically meaningful filtering criteria to detect novel candidate variants and loci for T2D and obesity. We have identified several known single nucleotide polymorphisms (SNPs) as markers for obesity (rs11960429), T2D (rs9379084, rs1126930), and body mass index (BMI) (rs115… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 52 publications
1
22
0
1
Order By: Relevance
“…Here we identify PLEKHA5, PLEKHA6 and PLEKHA7, and their ligand adaptor PDZD11, as proteins involved in the copper-dependent localization of ATP7A at the cell periphery and in the maintenance of copper homeostasis. PLEKHA5 and PLEKHA6 were first characterized as PH domain-containing proteins implicated in phosphoinositide signaling (Dowler et al, 2000), and genetic studies indicate that they participate in several developmental processes and diseases (Barbitoff et al, 2018;Cox et al, 2018;Daulagala et al, 2019;Fromer et al, 2014;Huang et al, 2020;Jamain et al, 2014;Jilaveanu et al, 2015;Liu et al, 2020;Shah et al, 2016;Spellmann et al, 2014;Tavano et al, 2018;Thapa et al, 2015;Wythe et al, 2011). However, little is known about the cellular localization and function of PLEKHA5 and PLEKHA6, and the molecular basis for the involvement of WW-PLEKHAs in physiological and pathological processes.…”
Section: Discussionmentioning
confidence: 99%
“…Here we identify PLEKHA5, PLEKHA6 and PLEKHA7, and their ligand adaptor PDZD11, as proteins involved in the copper-dependent localization of ATP7A at the cell periphery and in the maintenance of copper homeostasis. PLEKHA5 and PLEKHA6 were first characterized as PH domain-containing proteins implicated in phosphoinositide signaling (Dowler et al, 2000), and genetic studies indicate that they participate in several developmental processes and diseases (Barbitoff et al, 2018;Cox et al, 2018;Daulagala et al, 2019;Fromer et al, 2014;Huang et al, 2020;Jamain et al, 2014;Jilaveanu et al, 2015;Liu et al, 2020;Shah et al, 2016;Spellmann et al, 2014;Tavano et al, 2018;Thapa et al, 2015;Wythe et al, 2011). However, little is known about the cellular localization and function of PLEKHA5 and PLEKHA6, and the molecular basis for the involvement of WW-PLEKHAs in physiological and pathological processes.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports from Barbitoff et al () found a strong association of the rs6271 Arg549Cys polymorphism with Type 2 diabetes and obesity in Russia populations (Barbitoff et al ). Noradrenergic signaling has been implicated in Type 2 diabetes and obesity dating back to 1970 (Giachetti ; Munoz et al ; Commins et al ; Bozek et al ; Barbitoff et al ). Most of the work was performed in rodent models that noted that NE and DβH were drastically reduced in heart, kidney, and salivary glands in spontaneously diabetic mice (Giachetti ).…”
Section: Other Clinical Situations Involving Dβhmentioning
confidence: 97%
“…An intronic mutation rs3099797 in RREB1 has been identified as a candidate risk allele for T2D in Starr County Mexican-Americans [45]. In another Russian population based investigation, a coding region SNP rs9379084 (p. Asp1171Asn) in RREB1 shows strong association with T2D (p = 0.042) [46]. In 2014, a Genome-wide trans-ancestry meta-analyses containing populations from European, East Asian, South Asian, and Mexican and Mexican American ancestry discovered seven novel T2D susceptibility loci, and rs9505118 in RREB1 is one of them (p=1.4×10−9) [12].…”
Section: Rreb1 Is a Potential Risk Gene For Type 2 Diabetesmentioning
confidence: 98%